2015
DOI: 10.1210/jc.2014-2850
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Hospital Outcomes in Thyroid Storm: A Retrospective Cohort Study

Abstract: In acutely hospitalized thyrotoxic patients, the presence of central nervous system dysfunction distinguished clinically diagnosed TS from patients with BWS- or Ak-defined TS. Because TS patients had significantly worse outcomes in this study, thyrotoxic patients with possible TS and central nervous system dysfunction may derive the greatest benefit from aggressive supportive and TS-specific treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 23 publications
5
97
1
10
Order By: Relevance
“…Anxiety, agitation, delirium and coma are also commonly seen and are considered by many as essential to the diagnosis (4). In one study, altered mental status was the only reliable differentiating feature between thyroid storm and thyrotoxicosis (11). Cardiac manifestations include cardiac arrhythmias, congestive heart failure, hypotension and death may also occur from cardiovascular collapse (12).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety, agitation, delirium and coma are also commonly seen and are considered by many as essential to the diagnosis (4). In one study, altered mental status was the only reliable differentiating feature between thyroid storm and thyrotoxicosis (11). Cardiac manifestations include cardiac arrhythmias, congestive heart failure, hypotension and death may also occur from cardiovascular collapse (12).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment generally requires ICU monitoring and aims to restore thyroid gland function and at the same time diminish thyroid hormone effects on peripheral tissues with a combination of β blockers, thyrostatics, intravenous glucocorticoids, and eventually a high-dose of iodide compounds. 86 In a retrospective cohort study 87 of patients admitted to hospital with acute thyrotoxicosis, the presence of CNS dysfunction was the only significantly different clinical feature between patients with thyroid storm and those with compensated thyrotoxicosis. Thus, patients with thyrotoxicosis, possible thyroid storm, and altered mentation should be treated aggressively with supportive measures and antithyroid drugs.…”
Section: Diagnosis and Management Of Severe Primary Thyroid Disordersmentioning
confidence: 99%
“…The usefulness of the BWPS and JTA criteria has been compared by analyses of JTA nationwide surveys [4], and recently by 2 institutions that showed overall agreement between the 2 systems [21,22]. However, a report from the United States suggested that the BWPS ≥ 45 appeared to select a higher percentage of patients for aggressive therapy than the JTA criteria [21].…”
Section: Basic Policymentioning
confidence: 99%
“…However, a report from the United States suggested that the BWPS ≥ 45 appeared to select a higher percentage of patients for aggressive therapy than the JTA criteria [21]. Using both diagnostic systems to evaluate a patient's condition is recommended to increase the accuracy of clinical diagnosis and further validate the usefulness of these 2 sets of criteria.…”
Section: Basic Policymentioning
confidence: 99%